Remnants of Wehrmacht soldiers : burial and commemoration practices of German soldiers of the Second World War in Russia and Europe, 1941-2023 - Janz, Nina 1986- (Peter Lang, 2024)
"Today, fallen soldiers of the Second World War find their resting places across the globe. While many nations openly honor their military, Germany maintains a more reserved approach to its war dead. During the war, fallen soldiers were hailed as heroes, but after 1945, the treatment of the deceased and their graves underwent a profound transformation. Janz explores with a focus on the Eastern Front during wartimes and then post-war Soviet Union and Russian Federation this transformation from three key moments: 1. the treatment of the bodies, burial practices, and exhumations; 2. The burial sites, including cemetery construction and design; and 3. the realm of commemoration, encompassing memorial ceremonies and rituals. These rituals transition from the hero worship of Hitler's Wehrmacht to the mourning and reconciliation policies of the post-war West German government with Russia. This study offers a fresh examination of the German military dead, analyzing it based on diverse case studies within the framework of the controversies surrounding Wehrmacht soldiers and their challenging commemoration in the present day"--